Contrasting responses of rivers with different sizes to extrinsic changes in the northeastern Tibetan Plateau. (1st August 2022) - Feng, Zhantao; Peng, Tingjiang; Ma, Zhenhua; Han, Bingyan; Wang, Hong; Guo, Benhong; Zhao, Zhijun; Zhang, Jun; Song, Chunhui; Hu, Zhenbo
Graphical abstract: Highlights: The terrace sequences of Datong River were dated using multiple dating methods. Tectonic-climate forcing triggered the formation of the Datong River before ∼1.1 Ma. The Datong River has been more sensitive to climate changes than the Yellow River. Abstract: The formation of river terraces has been related to climate changes and surface uplift in the mountain regions. Although the formation mechanism of river terraces in the northeastern Tibetan Plateau has been extensively studied, the difference between the large river (trunk stream of Yellow River) and small rivers (tributaries of Yellow River) responding to external forcing is still poorly understood. Here, we employ multiple dating methods to date the terrace sequence of the Datong River in the northeastern Tibetan Plateau and then further correlate it with tectonic activity and climate records. Our results show that the modern Datong River in the Babaochuan Basin formed between 1.5 Ma and 1.1 Ma in response to the coupled effects of Asian monsoon enhancement and intense regional uplift. To further evaluate the effect of tectonic–climatic forcing on rivers of different scales, detailed comparison of terrace formation was carried out between the Datong River and Yellow River in the Lanzhou Basin. The comparison results indicate that under the context of relatively slow surface uplift during 0.6–0.13 Ma, the Datong River created three terraces probably ascribed to the glacial–interglacial cycles with high-amplitude fluctuations, whereas no terraces formed along the Yellow River in the Lanzhou Basin during the same interval. We conclude that the Datong River, as a smaller river than the trunk Yellow River, is probably more sensitive to the climate change.